Clinical efficacy of toothpaste containing potassium citrate in treating dentin hypersensitivity - Shih-Ya Shen; Chung-Hung Tsai; Li-Chiu Yang; Yu-Chao Chang (Elsevier, 2009)
Many adults suffer from sensitivity, and dentin hypersensitivity is most commonly the result of exposed dentin which can sometimes trigger pain or discomfort when eating, drinking or simply brushing. The purpose of this study was to evaluate the clinical efficacy of desensitizing toothpaste containing potassium citrate in treating dentin hypersensitivity. Materials and methods: This study was performed at the Department of Periodontics, Chung Shan Medical University Hospital. In total, 172 volunteers who provided informed consent were included in the study. A visual analog scale (VAS) was used to indicate dentin sensitivity in response to an air stimulus. Participants who had a VAS score of 30-80 were qualified for the study and were provided with their assigned desensitizing toothpaste containing potassium citrate (Colgate Sensitive Multi Protection) and a soft-bristled adult toothbrush for home use. After 4 weeks, the hypersensitive teeth were examined again, and the VAS score was also recorded. Results: In this study, 38% (65/172) participants were found to suffer from dentin hypersensitivity, 40 persons who reported VAS scores of 30-80 were qualified for the clinical trial. Among these, 34 (85%) participants reported reduced dentin hypersensitivity after using the desensitizing toothpaste containing potassium cit-rate for 4 weeks. The mean value of the VAS score prior to the use of the toothpaste was 50.72, while the mean value of the VAS score after use was 30.68. The use of Colgate Sensitive Multi Protection was found to significantly reduce dentin hypersensitivity after 4 weeks (P < 0.01). Conclusion: The prevalence of dentin hypersensitivity in this study was 38%. The use of desensitizing toothpaste containing potassium citrate with oral hygiene instruction can effectively reduce dentin hypersensitivity.